TEORI MULTIPLE INTELLIGENCES DAN IMPLIKASINYA TERHADAP PENGELOLAAN PEMBELAJARAN - Amir Hamzah (Institut Agama Islam Negeri Madura, 2009)
The article clarifies Howard Gardner's Multiple Intelligence theory. He states that the theory serves nine kinds of intelligences---linguistic, logical-mathematical, spatial, bodilykinestheticc, musical, interpersonal, intrapersonal, naturalistic, and existential. The theory claims that infants have different intelligences, moreover it influences learning orientation. It enables students to comprehend the subjects more easily, if the subjects are presented based on the students' potencies. Yet, it is important for the teachers to understand the theory to accelerate the learning process and output.